PENGEMBANGAN E-MODUL PADA MATERI TRIGONOMETRI SISWA KELAS X SMA N 1 PAJANGAN - Tyas Wati Ardiansah; Nendra Mursetya Somasih Dwipa (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
This research aims to develop an e-module assisted by Macromedia Flash 8 which is feasible (valid, practical, and effective) to be used in learning the rules of sins and cosines of trigonometry for high school students in class X. The research was conducted at SMAN 1 Pajangan, which is located in Guwosari, Pajangan, Bantul in the academic year 2021/2022. This research is a development research that uses the Brog and Gall method using 10 stages of research, namely: research and information collecting, planning, developing primary from product, premilinary field testing, main product revision, main field testing, operational product revision, operation field testing, final product revision, desimination and implementation. The main sample of the research was 30 students of class X MIPA 3. The data collection technique of this research used a questionnaire, namely a questionnaire for expert validation and a student response questionnaire to see the practicality of the e-module. The data analysis technique used is a qualitative analysis technique for compiling data reduction, while other analytical techniques are used in a qualitative descriptive manner to present data in the form of numbers and tables. The results of the research concluded that the e-module assisted by Macromedia Flash 8 was feasible because material experts and e-module experts stated that the module was valid with an average score of 4.35 and 4.65 with the criteria of "Very Good". Based on the students' responses, they stated that they were practical with a good response percentage of 83%, and based on the average student score above the KKM, the average score of 25 students was 72.5.